Aspergillus sensitisation in bidi smokers with and without chronic obstructive lung disease. Issue 6 (31st January 2017) - Agarwal, Ritesh; Bhogal, Sumita; Choudhary, Hansraj; Aggarwal, Ashutosh N.; Sehgal, Inderpaul S.; Dhooria, Sahajal; Behera, Digambar; Chakrabarti, Arunaloke
Summary: Recent studies have described fungal sensitisation in patients with chronic obstructive pulmonary disease (COPD). However, no study has evaluated fungal sensitisation specifically in bidi smokers. Herein, we evaluate the prevalence of Aspergillus sensitisation in bidi smokers. Bidi smokers with and without COPD underwent chest radiography, spirometry, Aspergillus skin test, A. fumigatus precipitins, A. fumigatus ‐specific IgE and total IgE. Aspergillus sensitisation was defined as the presence of either immediate cutaneous hyperreactivity to Aspergillus antigen or raised A. fumigatus ‐specific IgE level >0.35 kUA/L. Bidis were obtained from a subset of cases and controls and cultured for the growth of any fungus. Two hundred subjects with COPD and 72 chronic bidi smokers without COPD were included in the study (258 men; mean age, 56.8 years). Aspergillus sensitisation was found to be significantly higher in bidi smokers without COPD (27.8%) compared to the COPD cases (16%). Age, COPD, lung function, severity of smoking and current smoking were not associated with Aspergillus sensitisation, on a multivariate logistic regression analysis. We found a high prevalence of Aspergillus sensitisation in bidi‐smoking subjects. More studies are required to confirm the findings of our study.